1996
DOI: 10.1111/j.1545-5300.1996.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

“Speech After Long Silence”: The Use of Narrative Therapy in a Preventive Intervention for Children of Parents with Affective Disorder

Abstract: This article is an attempt to explain why the stories of those who suffer from affective disorder have gone unspoken, and to describe how the Preventive Intervention Project (PIP) helps to elaborate a narrative process within families. The PIP is a short-term, psychoeducational intervention focused on enhancing family understanding of affective disorder, and on building resiliency in children. Detailed descriptions of interventions with two families are used to demonstrate how the PIP works with parents and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 22 publications
1
46
0
1
Order By: Relevance
“…Recent literature notes the importance in adolescent development of moving from dependence on parents toward interdependence, but not total independence [6,27]. Similarly, previous research [39] has identified the importance of dialogue in helping facilitate family adjustment to chronic illness. With this goal in mind, clinical research needs to address how to help parents remain involved in their adolescents' management of type 1 diabetes in the least conflict-laden and most supportive ways.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature notes the importance in adolescent development of moving from dependence on parents toward interdependence, but not total independence [6,27]. Similarly, previous research [39] has identified the importance of dialogue in helping facilitate family adjustment to chronic illness. With this goal in mind, clinical research needs to address how to help parents remain involved in their adolescents' management of type 1 diabetes in the least conflict-laden and most supportive ways.…”
Section: Discussionmentioning
confidence: 99%
“…Focht & Beardslee, 1996;FochtBirkerts & Beardslee, 2000) also show that initiating communication about PMHP can often be a challenging task for parents, partly because of feelings of guilt and shame and partly because of the difficulty of finding appropriate words to describe MHP. Focht-Birkerts & Beardslee (2000) observed that the pain of the children seemed to be "bulging through the seams of the 'not-yet-said'" (p. 421).…”
Section: Introductionmentioning
confidence: 99%
“…The "attitude change" question regarding increases in understanding of feelings about their child's heart disease and inter-family supportiveness further bolster the use of the EJ as a sounding board for mothers to compare and contrast their own experiences and their child's feelings/behavior. All of these factors have all been identified as important to both successfully navigating medical crises (Shapiro & Koocher, 1996) and in developing self-understanding (Focht & Beardslee, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Based upon this work, an effective preventive intervention needs to include a focus on self-understanding and shared understanding. Self-understanding has proven an important component of resiliency in previous studies (Beardslee, 1989;Focht & Beardslee, 1996). The design of a computer program as a preventive intervention needs to go beyond the simple expression of factual information to one that allows an individual to not only read the stories of others, but also allow them the opportunity to tell their own story.…”
mentioning
confidence: 99%